Fracturas de ángulo mandibular asociada a extracción del tercer molar - Espinoza Rodríguez, Alexis Andrés (2023)
ABSTRACT: The analysis of angle fractures associated with the extraction of a third molar was carried out through a scientific literature review process, which included scientific articles such as bibliographic reviews, case studies, and meta-analyses, in scientific databases such as Google Scholar, Science Direct, Wiley and Springer, within a time frame of the last ten years, so that those articles in which the quality of each publication was assessed were selected. Angle fractures due to lower third molar extraction is a complication with a shallow rate in dentistry. An impacted and partially erupted lower third molar occupies space that should be bone thus decreasing the area's density. On the other hand, osteoporosis and other bone-related disorders further damage the mandible, making it more prone to fractures.